The Analysis of Factors Affecting the Income of Dwarf Coconut Farmers in Siwalubanua II Village - Rifai, Rizal Nurdin; Hermanto, Bambang (Universitas Medan Area, 2025)
This study aims to analyze the factors influencing the income of dwarf coconut farmers in Siwalubanua II Village, Gunungsitoli Idanoi District, focusing on three main variables: production costs, selling price, and land area. The research employed a quantitative approach using multiple linear regression analysis. The sample consisted of 51 dwarf coconut farmers. The results indicate that production costs, selling price, and land area have a significant effect on farmers’ income. Among these factors, the selling price of coconuts has the greatest impact on income, followed by land area and production costs. Therefore, the study suggests that farmers should optimize production costs, expand their cultivated land, and maintain the quality of their coconuts to sustain favorable selling prices and increase income. These findings may also serve as a reference for policymakers in designing programs aimed at improving the income of coconut farmers.